A review of models for assessing readiness of construction organisations to innovate. Issue 2 (26th August 2020) - Akunyumu, Stephen; Fugar, Frank D.K.; Adinyira, Emmanuel; Danku, James Cofie
Abstract : Purpose: There is an urgent need for the construction industry to improve its current performance to increase productivity and satisfy the complex and varying needs of project clients. To be successful, construction companies must innovate. Unfortunately, the extant literature has revealed some inertia towards innovation which in several cases is because of lack of the organisational readiness required to embrace innovation. Various models for assessing organisational readiness are proposed in the literature. Accordingly, the purpose of this paper is to determine the applicability of existing models for assessing the readiness of construction organisations to innovate. Design/methodology/approach: A desk study of the extant literature was conducted to identify perspectives of readiness assessment and, based on a comparative framework, a set of readiness assessment models identified was examined to ascertain their perspectives on organisational readiness assessment. Findings: Five models/tools of organisational readiness assessments were identified and compared based on a set of identified criteria. The comparative analysis revealed that three of the models can be used to assess the readiness of construction organisations to innovate, albeit with varied scopes of modification. Practical implications: The paper presents an overview of readiness assessment perspectives developed through models that could help organisations in selecting the most appropriate tool to assess their readiness. Originality/value: The paper uses a comparative framework as a basis for analysing the identified models. It further discusses the strengths and weaknesses inherent in each model noting critical areas of omission.